The hegligent murder aggravated by the inebriation or the influence of substances that produce physical or psychic dependence (2014)
The first section of this article presents an overview on the problems discussed by Colombian legal scholars in relation to the crime of involuntary manslaughter aggravated by inebriation or the influence of substances that produce physical or psychologic